Sustainability in the Global-Knowledge Economy - Torrent-Sellens, Joan; Sainz-González, Jorge (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Knowledge affects all aspects of the economy, but digitalization probably represents the most ubiquitous of its appearances. This book analyzes, from a constructive point of view, some of its applications, extracting lessons to maximize its utility and exporting its use to other sectors. It also shows the caveats of its applications, allowing managers to learn its difficulties and how to overcome them from real-life cases. All the information is presented in an academic and rigorous way and represents an excellent starting point to study the effects of digitalization for both practitioners and researchers.